Titanium-based potassium-ion battery positive electrode with extraordinarily high redox potential - Stanislav S. Fedotov (Nature Portfolio, 2020)
The Ti4+/Ti3+ redox couple is usually a good choice for anodes due to its low potential. Here, the authors show that the potential can be increased to nearly 4.0 V in KTiPO4F, which serves as a high-performance cathode for K-ion batteries.